Print media innovation in the digital era: disruptive challenges or opportunities? - Pamuji, Eko; Ida, Rachmah; Mustain (Faculty of Communications Science, Dr. Soetomo University, 2022)
The newspaper industry (print media) has many difficulties in the digital era. Print media’s demise has been facilitated by the emergence of digital media, specifically new internet-based media. Newspapers and other traditional mass media outlets have issues. Digital media is both a challenge and a threat to traditional media, particularly newspapers. Due to these obstacles and dangers to print media, some publications have shut down, and others have switched to digital editions. This study aims to ascertain how the print media in East Java (Jawa Pos and Surya) retain their commercial viability under the continuing media digitalisation competition. With a Marxist Media perspective, this study employs a qualitative methodology. From July 2020 to July 2022, researchers used in-depth interviews and direct observation to collect data. East Java newspapers Jawa Pos and Surya were the focus of this study. The study’s findings demonstrate that the media products produced by these two media businesses engage in significant product commodification to create worldwide products. To produce global products, the two media have also produced media products. These products include news content that employs a single source for three different media types: print, electronic (television, radio), and internet media.